Pengaruh Partisipasi dalam Penyusunan Anggaran Terhadap Kepuasan Kerja dan Kinerja Manajer - Abriyani Puspaningsih (Jurnal Akuntansi dan Auditing Indonesia, 2002)
The objective of this paper is to discuss the effect of budget participation on job satisfaction and managers’ performance. The discussion of this study describes the relationship impact budget participation on job satisfaction and managers’ performance through intervening variables (role ambiguity, job relevan information) and moderating variables (job difficulty, locus of control or culture dimension) directly and indirectlyKey words: Budget participation, job satisfaction, and manager’s performance.